2002
DOI: 10.1002/bmc.163
|View full text |Cite
|
Sign up to set email alerts
|

LC‐ESI‐MS analysis of taxoids from the bark of Taxus wallichiana

Abstract: LC-ESI-MS analysis was carried out for taxoid profiling of partially purified methanol extracts of the stem bark of Taxus wallichiana growing in different regions of the Himalayas (Kashmir, Himachal Pradesh, UP hills, Sikkim and Arunachal Pradesh). Cone voltage fragmentation of the protonated, ammonium or sodium cationized molecular species resulted in diagnostic fragment ions. Thus, information about the number and nature of substituents and the taxane skeleton (whether it is normal or rearranged) was readily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
(18 reference statements)
2
23
0
Order By: Relevance
“…However, the contents of other taxoids such as 10-DAB III and 7-xyl-10-DAT are much higher than paclitaxel in Taxus species, and pharmacological experiments have indicated that some of them, such as 7-xyl-10-DAT, exert strong anti-tumor activity (Lataste et al, 1984). These taxoids are precursors necessary for the biosynthesis of paclitaxel in the plants (Madhusudanan et al, 2002b;Zu et al, 2006;Ballero et al, 2003;Mroczek and Glowniak, 2001). Therefore, these taxoids have become one of the hot spots in the field of paclitaxel research in recent years.…”
Section: Simultaneous Determination Of Main Taxoids Inmentioning
confidence: 98%
“…However, the contents of other taxoids such as 10-DAB III and 7-xyl-10-DAT are much higher than paclitaxel in Taxus species, and pharmacological experiments have indicated that some of them, such as 7-xyl-10-DAT, exert strong anti-tumor activity (Lataste et al, 1984). These taxoids are precursors necessary for the biosynthesis of paclitaxel in the plants (Madhusudanan et al, 2002b;Zu et al, 2006;Ballero et al, 2003;Mroczek and Glowniak, 2001). Therefore, these taxoids have become one of the hot spots in the field of paclitaxel research in recent years.…”
Section: Simultaneous Determination Of Main Taxoids Inmentioning
confidence: 98%
“…The best solvent was found to be 80% ethanol which allowed extraction of all the taxoids in high yields, while pure ethanol could not extract the taxoids efficiently. During this process, methanol was also investigated because it is broadly applied in the studies of paclitaxel [7,20,22,23,30,31]. In most of these papers only methanol was applied as an extraction solvent without performing a comparison with ethanol, but pure or aqueous ethanol was also used in some papers [16,32].…”
Section: Extractionmentioning
confidence: 99%
“…As a result of recent advances in electrospray ionization (ESI) [1,26] and atmospheric pressure ionization (API) techniques, liquid chromatography coupled with tandem mass spectrometry (LC-MS-MS) has emerged as an efficient analytical tool with improved sensitivity, selectivity, and specificity. The usefulness of this technique has been demonstrated for a wide range of applications in bioanalytical, environmental, and pharmaceutical research [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as one of the most useful anticancer drugs of plant origin available today. It is effective in the treatment of many tumor types, such as ovarian, breast, melanoma, head, neck, bladder, gastrointestinal, lung cancer, and non-small-cell lung cancer [1][2][3], as well as for AIDS-related Kaposi's sarcoma [4][5][6]. Its fundamental anticancer mechanism is unique [7].…”
Section: Introductionmentioning
confidence: 99%